1999
DOI: 10.1111/j.1478-3231.1999.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of hepatitis C viremia to HIV state and to infection by specific hepatitis C genotypes

Abstract: Infection by specific HCV genotypes (type 3 in HIV-infected patients and by type 1 in HIV-non infected ones) implies a higher risk of HCV viremia, whereas multiple HCV types infection is negatively associated with this probability. HIV coinfection does not influence the probability of HCV viremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A vigorous host CD4/CD8 T-lymphocyte reponse is likely important in controlling HCV RNA levels and HIV-coinfected patients have been shown to mount a less vigorous T-cell response to HCV than monoinfected patients [27,28]. Although some investigators have demonstrated an inverse relationship between CD4 T-cell count and HCV RNA levels [5,14], our results and those of others did not show this [29,30]. CD4 T-cell count alone may be an incomplete measure of the quality of the immune response in HIV infection as evidenced by opportunistic infections such as tuberculosis occurring at CD4 cell counts >200 cells/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vigorous host CD4/CD8 T-lymphocyte reponse is likely important in controlling HCV RNA levels and HIV-coinfected patients have been shown to mount a less vigorous T-cell response to HCV than monoinfected patients [27,28]. Although some investigators have demonstrated an inverse relationship between CD4 T-cell count and HCV RNA levels [5,14], our results and those of others did not show this [29,30]. CD4 T-cell count alone may be an incomplete measure of the quality of the immune response in HIV infection as evidenced by opportunistic infections such as tuberculosis occurring at CD4 cell counts >200 cells/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Immune competence has been hypothesized to be central to the spontaneous resolution of HCV and control of HCV viremia [7,8]. Nevertheless, whether and how HIV infection and HIV-related factors, e.g., CD4 T-cell count, HIV viral load, and the use of and response to HIV antiretroviral therapy (ART), are associated with spontaneously resolved HCV infection and HCV RNA levels in persistent HCV infection among IDUs is controversial [5,[9][10][11][12][13][14][15]. The virological characteristics and epidemiology of HCV in HIV-coinfected IDUs are of increasing clinical importance, as more coinfected patients are presenting for HCV care and consideration for HCV antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The potential role of HCV genotype posited by a few authors is unlikely in our study, because the distribution was not different between the 2 groups. 5,32,33 In conclusion, liver fibrosis is worse in HIV-HCV patients than in HCV patients, even with low-level immunodepression, justifying early treatment against HCV. In this setting of coinfection, both fibrous septa and perisinusoidal fibrosis are more abundant, so we recommend the use of adequate special stains (trichrome stain plus picrosirius red or Gordon and Sweet's stain) for histological examination of biopsy specimens.…”
Section: Fibrosis In Hcv (Rullier Et Al)mentioning
confidence: 99%
“…However, a direct relationship between the level of viremia and either the severity of liver disease or transaminase levels is not universally accepted (10,11). Besides, the roles of HCV genotype, human immunodeficiency virus (HIV) coinfection, age, race, and sex have been investigated in this respect, with various results (1,2,(15)(16)(17)22).…”
mentioning
confidence: 99%